Keunggulan Metode Demonstratif Terhadap Metode Retorika Dan Dialektika: Menguak Metode Kritik Filsafat Ibn Rusyd - Bistara, Raha (Universitas Islam Negeri Raden Intan Lampung, 2021)
This article shows how the demonstrative method (burhani) is more superior to rhetoric (khatabbi) and dialectic method (jaddali), the use of the demonstrative method is based on the utilization of the mind. Ibn Rusyd stated that the demonstrative method is considered the right method for seeking the answers above the questions on the subject of religion and philosophy. However, it is not amazed Ibn Rusyd used a demonstrative method to criticize the Mutakallimun Ash’ariyah and his followers especially Imam Al-Ghazali. Ibn Rusyd also criticized Ibn sina and Zahiriyah group with the method they used. There was confusion for the answer to who they presented regarding religious and philosophical problems. While there were many problems with their views especially in their books. This article used the library research method which uses literature either in the form of books, or notes from previous research reports. While the sources of this research there are two sources as primary source and secondary sources. This result of this research revealed that Ibn Rushd’s philosophy critical method from authentic sources related to the problem. Although, by the use of various sources used, it is hoped there will be a new finding related to demonstrative method initiated by Ibn Rushd in refuting the arguments of rhetorical and dialectical groups which are not deep, explicit, and simple. As well as providing the new formulas that are fresher and more varied concerning the answer about the problems of religion and philosophy.